Risk Assessment and Outcome of Venous Thromboembolism in Pediatric Population in an Academic Care Center of a Low-Middle Income Country. (16th February 2021) - Sadiq, Muhammed Wahhaab; Ukrani, Ronika Devi; Arif, Aiman; Akbar, Inaara; Altaf, Sadaf; Moiz, Bushra
Venous thromboembolism (VTE) is a recognized complication of hospital stay in young patients in many developed countries, but such an information is largely unavailable from a low middle-income country (LMIC). This study aimed at identifying the frequency, risk factors, treatment options and outcome of deep venous thrombosis/pulmonary embolism (DVT/PE) in pediatric population in a tertiary care center from a LMIC. International classification of disease, ninth revision (ICD-9) was used to identify VTE in patients aged 0-18 years during January 2011 to September 2019. In-house computerized system was used to collect data for demographics, clinical and laboratory details. SPSS version 19 was used to analyzed data. The study was approved by Institutional ethical review committee (3872-Pat-ERC-15). During the study period, 134617 pediatric patients were hospitalized, DVT/PE was observed in 77 unique patients (47 males and 30 females) with a median (IQR) age of 14 (5-16) years equivalent to 5.9 VTE events /10, 000 hospital admissions. Malignancy, community acquired infections and autoimmune diseases were the predominant risk factors (75%) in adolescent age-group while surgery for congenital heart anomalies was the primary reason (71%) in infants. Overall, lower extremity thrombosis was the most frequent (51%) followed by pulmonary embolism (25%). and upper extremity thrombosis (24%). Enoxaparin and unfractionated heparin were mainly used to treat VTE and all-cause mortality was 13% in the cohort studied. We observed substantial VTE events in pediatric patients during their hospital stay in a tertiary care center of a low-middle income country.